2002
DOI: 10.1136/heart.87.2.e1
|View full text |Cite
|
Sign up to set email alerts
|

Reversible left ventricular dysfunction "takotsubo" cardiomyopathy associated with pneumothorax

Abstract: An 83 year old woman presented to the emergency department with chest pain and dyspnoea. Chest radiography showed pneumothorax of the left lung. Arteries were normal on coronary angiography. Left ventriculography showed asynergy of apical akinesis and basal hyperkinesis. Within 18 days, the asynergy improved without any specific treatment. In the present case the left ventricular dysfunction may have been induced by altered catecholamine dynamics as a result of pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…5) Takotsubo-shaped hypokinesis of the left ventricle has been documented in patients in Japan; it is characterized by an apical wall motion abnormality, sometimes in the absence of coronary artery disease. 6) Akashi, et al 7,8) reported takotsubo-shaped hypokinesis following an episode of polymorphic ventricular tachycardia especially with a short coupling interval, and following an episode of pneumothorax of the left lung. Our patient did not complain of palpitations, there were no signs of arrhythmia, and the chest X-ray findings were normal.…”
Section: Discussionmentioning
confidence: 99%
“…5) Takotsubo-shaped hypokinesis of the left ventricle has been documented in patients in Japan; it is characterized by an apical wall motion abnormality, sometimes in the absence of coronary artery disease. 6) Akashi, et al 7,8) reported takotsubo-shaped hypokinesis following an episode of polymorphic ventricular tachycardia especially with a short coupling interval, and following an episode of pneumothorax of the left lung. Our patient did not complain of palpitations, there were no signs of arrhythmia, and the chest X-ray findings were normal.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the association with spontaneous pneumothorax has already been found 10 , there is a strong evidence in that report suggesting pneumothorax due to accident during central vain puncture, as pneumothorax was not seen in the first radiography. The patient was sent with thoracic draining, optimization of volemia and vaso- active drugs, for the stabilization of vital signs and fast sent to hemodynamics laboratory for a possible intervention.…”
Section: Case Reportmentioning
confidence: 78%
“…In 2002, Akashi, et al reported the second case. 10 It presents a transient and reversible left ventricular contractile dysfunction with an acute beginning of symptoms mimickings those of a myocardial infarction. 5,11 The name Takotsubo or apical ballooning derives from the distinctive morphology of the left ventricle during the endsystole resembling an octopus fishing vessel with round bottom and narrow neck (the "takotsubo" in Japanese).…”
Section: Discussionmentioning
confidence: 99%